Understanding Uneven Land Subsidence in Beijing, China, Using a Novel Combination of Geophysical Prospecting and InSAR. Issue 16 (21st August 2020) - Guo, Lin; Gong, Huili; Li, Jiwei; Zhu, Lin; Xue, Aimin; Liao, Lin; Sun, Ying; Li, Yongsheng; Zhang, Zhenxin; Hu, Leyin; Gao, Mingliang; Zhou, Chaofan; et al.
Abstract: A novel approach was developed to quantitatively examine land subsidence. It combines a new geophysical (NG) prospecting and the interferometric synthetic aperture radar (InSAR) technology to explore uneven development of land subsidence in Beijing, China. We derived land subsidence spatial information over 4 years (from November 2014 to July 2018) based on Sentinel‐1 satellite imagery and the small‐baseline InSAR (SBAS‐InSAR) method. Also, profile data were acquired using seismic frequency resonance (SFR) approach in a few settlement areas. We developed a geological model based on boreholes and SFR data. Thus, we can quantitively study the driving forces of a typical uneven land subsidence. We found that faults are controlling spatial developments of land subsidence in Beijing. The subsidence rates have different values along the same fault. Also, we revealed the contributions of compressible layers to the formation of uneven land subsidence. Plain Language Summary: Due to long‐term exploitation of groundwater, severe land subsidence has occurred in Beijing, China. Land subsidence is a complex geological hazard caused by multiple driving forces, including groundwater pumping, dynamic loads, and mining. Understanding the mechanisms causing land subsidence has a great significance to sustainable development of regional economy. We innovatively combine seismic frequency resonance (SFR) and interferometric synthetic aperture radar (InSAR) technologies to quantitatively explore the mechanisms responsible for uneven subsidence in Beijing. We used radar images from November 2014 to July 2018 and adopted the small baseline InSAR (SBAS‐InSAR) method to monitor the land surface displacements of the Beijing Plain. Also, formation density information in typical areas were acquired using the SFR approach. Then, we used the hydrogeological data to understand the geophysical information of the profile. By combing these new data, we can quantitively examine the driving forces of a typical uneven land subsidence. We found that faults are controlling the spatial development of land subsidence. In addition, we discovered the distribution of compressible layers and characteristics of faults. Our research provides a widely applicable method to study the mechanisms of land subsidence. Key Points: We present a novel approach to deeply explore land subsidence development Multiple faults are controlling the uneven development of land subsidence Seismic frequency resonance interpretations reveal the contributions of compressible layers in land subsidence